Advanced Oxidation Protein Product Promotes Oxidative Accentuation in Renal Epithelial Cells via the Soluble (Pro)renin Receptor-Mediated Intrarenal Renin-Angiotensin System and Nox4-H2O2 Signaling. (26th November 2021) - Xue, Kai; Wang, Yurong; Wang, Yan; Fang, Hui
Abstract : Full-length (pro)renin receptor (fPRR), a research hotspot of the renin-angiotensin system (RAS), plays a serious role in kidney injury. However, the relationship between fPRR and advanced oxidation protein product (AOPP) remains largely unexplored. This study was aimed at exploring the effect of fPRR, especially its 28 kDa soluble form called soluble PRR (sPRR), in AOPP-induced oxidative stress in HK-2 cells, a renal proximal tubular epithelial cell line. Incubation of HK-2 cells with 100 μ g/ml AOPP resulted in significant upregulation of fPRR expression and caused an approximately fourfold increase in medium sPRR secretion. However, unmodified albumin did not demonstrate the same effects under the same concentration. Treatment of HK-2 cells with the site-1 protease (S1P) inhibitor PF429242 (40 μ M) or S1P siRNA significantly inhibited AOPP-induced sPRR generation. fPRR decoy inhibitor PRO20 and PF429242 treatment for 24 h remarkably attenuated the AOPP-induced upregulation of RAS components. Furthermore, PF429242 significantly reduced the AOPP-stimulated expression of NADPH oxidase 4 (Nox4) and H2 O2 expression. The use of a small recombinant protein, named sPRR-His, reversed these alterations. In conclusion, these results provided the first demonstration of AOPP-promoted activation of sPRR. Increased renal proximal tubule Nox4-derived H2 O2 contributed to the aggravation of oxidative stress. Targeting S1P-derived sPRR is a promising intervention strategy for chronic kidney disease.